A kind of dry powder machine-made sand low-carbon concrete and preparation method thereof
By using composite powder materials such as activated limestone powder and modified rice husk ash in concrete production to replace part of cement, the problem of high carbon emissions in concrete production is solved, and a low-carbon and environmentally friendly production effect is achieved.
Patent Information
- Application Number
- CN202311866059.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-12-29
AI Technical Summary
A large amount of carbon dioxide emissions are generated during the existing concrete production process, resulting in a large environmental pollution and a large carbon footprint.
The preparation method of dry powdered machine sand low-carbon concrete is adopted, and carbon emissions are reduced by using composite powder materials such as activated limestone powder and modified rice husk ash instead of some cement.
On the premise of ensuring the strength and durability of concrete, the amount of cement is reduced by about 70%, thereby significantly reducing carbon emissions in the concrete production process and achieving low-carbon and environmentally friendly production requirements.
Smart Images

Figure CN117776628B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of building construction materials, and more specifically, to a dry powder machine-made sand low-carbon concrete and a preparation method thereof. Background Art
[0002] Concrete is a building material widely used in construction, roads, bridges and other engineering fields. It is made by mixing cement, sand, gravel and water, and is made through processes such as mixing, pouring and curing.
[0003] In the process of concrete production and use, a large amount of energy and resources are consumed, and a large amount of greenhouse gases such as carbon dioxide are also emitted, which has a negative impact on the environment. In particular, CO2 emissions from cement production usually account for 510% of carbon emissions from human activities. The cement industry is the main source of carbon emissions in my country, accounting for about 15%. Every ton of silicate cement produced emits about 511kg of CO2 from cement raw materials. Therefore, the cement industry is a veritable carbon emitter. The emission of a large amount of carbon dioxide not only destroys the living environment of human beings, but also greatly damages human health. Therefore, how to reduce the carbon emissions of concrete and improve its environmental performance has become an important research direction in the current concrete field. Summary of the invention
[0004] In order to reduce carbon emissions during the production and use of concrete, the present application provides a dry powder machine-made sand low-carbon concrete and a preparation method thereof.
[0005] In the first aspect, the present application provides a dry powder machine-made sand low-carbon concrete, which adopts the following technical solution:
[0006] A dry powder machine-made sand low-carbon concrete, characterized by comprising the following raw materials in parts by weight:
[0007] 20-30 parts of cement;
[0008] 30-60 parts of fly ash;
[0009] 30-60 parts of mineral powder;
[0010] Recycle glass powder 10-30 parts;
[0011] 30-60 parts of nano calcium carbonate;
[0012] Silica fume 10-30 parts;
[0013] 70-90 parts of composite powder material;
[0014] 600-800 parts of machine-made sand;
[0015] 800-1000 parts of crushed stone;
[0016] 150-157 parts of water;
[0017] 5-10 parts of admixture;
[0018] The composite powder material is obtained by mixing activated limestone powder and modified rice husk ash;
[0019] The activated limestone powder is obtained by grinding, calcining, curing and pulverizing limestone powder;
[0020] The modified rice husk ash is obtained by soaking, calcining and pulverizing rice husk.
[0021] By adopting the above technical scheme, cement: as the main cementitious material, cement reacts with water to form cement paste, which binds aggregates together and provides strength after the concrete solidifies. However, the production process of cement as the main cementitious material will generate a large amount of carbon dioxide emissions. Therefore, by adding other powder materials to replace part of the cement, the demand for cement can be reduced, thereby reducing carbon dioxide emissions. Fly ash and mineral powder are the reuse of industrial waste. Their use can play a better gelling role, thereby reducing the consumption of natural resources and reducing carbon dioxide emissions. Recycled glass powder can replace part of the cement, reduce the amount of cement used, and thus reduce carbon dioxide emissions. At the same time, recycled glass powder can improve the strength and durability of concrete. Nano calcium carbonate, as a filling material, can improve the strength and durability of concrete, while reducing the demand for cement and reducing carbon dioxide emissions.
[0022] The composite powder material is obtained by compounding activated limestone powder and modified rice husk ash. Activated limestone powder is obtained by grinding, calcining, curing and pulverizing limestone powder. Since the activity of limestone powder itself is low, it is not conducive to exerting its gelling properties. After activation, calcium carbonate particles are treated in a liquid phase state, and calcium carbonate can be evenly coated with sulfate powder, and then fully dispersed on the surface of calcium carbonate particles through steric effect and double electric layer effect. The distance between particles is increased, and the secondary coagulation of particles is reduced during dehydration and drying, thereby improving the reaction ability of calcium carbonate and finally forming highly active activated limestone powder. Modified rice husk ash is obtained by soaking, calcining and pulverizing rice husk. Rice husk is the reuse of agricultural waste. Its use can reduce the waste of agricultural resources and reduce carbon dioxide emissions. In addition, modified rice husk ash is conducive to improving the bonding force between various cementitious materials and aggregates, thereby ensuring the strength performance and durability of low-carbon concrete.
[0023] By using the above-mentioned raw materials and other powder cementitious materials, the amount of cement per cubic meter of concrete can be reduced by about 70% on the original basis, thereby greatly reducing the carbon emissions of concrete in the production process, which is conducive to achieving low-carbon and environmentally friendly production requirements.
[0024] Optionally, the weight percentage of activated limestone powder in the composite powder material is 50-70%.
[0025] By adopting the above technical solution, by controlling the mass proportion of activated limestone powder in the composite powder material, the activity and reaction performance of concrete can be adjusted, thereby improving the strength and durability of concrete. When the mass proportion of activated limestone powder is high, the activity and reaction performance of concrete are better, but the cost is also relatively high; when the mass proportion of activated limestone powder is low, the cost of concrete is low, but the activity and reaction performance are also relatively poor. Controlling the proportion of activated limestone powder within the above range can control the production cost of concrete while ensuring the strength and durability of concrete, thus having better practical significance and promotion.
[0026] Optionally, the activated limestone powder is prepared by the following method:
[0027] S1. Grinding: Grind the limestone powder in a ball mill to form fine powder;
[0028] S2, calcination: calcining the ground limestone powder and sulfate powder at 900-1250° C. for 1-2 hours to obtain a calcined material;
[0029] S3, soaking: soak the calcined material in water and cure it at 30-50°C;
[0030] S4. Powdering: After the curing is completed, the soaked slurry is dried and then ball-milled to obtain activated limestone powder.
[0031] By adopting the above technical scheme, the limestone powder is fully ground in a ball mill to form fine powder. The grinding process can reduce the particle size of the limestone powder, increase its specific surface area, and thus improve its reactivity. The ground limestone powder and sulfate powder are calcined at 900-1250°C. During the calcination process, the calcium carbonate in the limestone powder will decompose into calcium oxide and carbon dioxide. At the same time, the sulfate in the sulfate powder will react with the calcium oxide to form calcium sulfate. This reaction will form a calcium sulfate phase in the calcined material, which improves the reactivity of the limestone powder. The calcined material is soaked in water and cured at 30-50°C. During the curing process, the calcium oxide in the calcined material will react with water to form calcium hydroxide. Calcium hydroxide can further react with sulfate to form a more stable calcium sulfate phase. This process can further improve the reactivity of the limestone powder. After the curing is completed, the soaked slurry is dried and then ball-milled to obtain activated limestone powder. The pulverization process can crush the cured limestone powder into fine powder for better dispersion and reaction in concrete.
[0032] Optionally, the sulfate powder in S2 is any one of magnesium sulfate, barium sulfate and copper sulfate.
[0033] By adopting the above technical scheme, the activity of limestone powder can be fully improved by the above three types of sulfate powder, so that the limestone powder can exert better cementing properties, and the above sulfate powder is beneficial to reduce alkali-aggregate reaction, which is beneficial to fully improve the strength and durability of concrete.
[0034] Optionally, the mass ratio of limestone powder to sulfate powder in S2 is 1:(0.01-0.2).
[0035] By adopting the above technical solution, the activity of activated limestone powder can be adjusted by controlling the mass ratio of limestone powder to sulfate powder, thereby improving the strength and durability of concrete. When the amount of sulfate powder used is small, the activity of activated limestone powder is low, but the cost is also relatively low; when the amount of sulfate powder used is large, the activity of activated limestone powder is high, but the cost is also relatively high.
[0036] Optionally, the modified rice husk ash is prepared by the following method:
[0037] The rice husk is soaked in a NaOH solution for 0.5-1h, the straw is repeatedly washed with water and then air-dried, then calcined at 600-1000°C, and then pulverized to obtain highly active modified rice husk ash.
[0038] By adopting the above technical scheme, highly active modified rice husk ash can be prepared by soaking, rinsing, drying, calcining and pulverizing rice husk in a NaOH solution, thereby improving the strength and durability of concrete.
[0039] In the soaking step, using a NaOH solution with a mass concentration of 3-5% can remove impurities on the surface of the rice husk and make the cellulose and other substances in the rice husk more loose, thereby improving its activity. In the calcining step, the rice husk is calcined at 600-1000°C, which can cause the cellulose and other substances in the rice husk to undergo a pyrolysis reaction to generate highly active substances. In the pulverizing step, the calcined rice husk is pulverized to make the particle size of the modified rice husk ash finer, thereby improving its activity.
[0040] Optionally, the mass concentration of the NaOH solution is 3-5%.
[0041] By adopting the above technical solution and using a NaOH solution with a mass concentration of 3-5%, impurities on the surface of the rice husk can be removed, and substances such as cellulose in the rice husk can be made looser, thereby improving its activity.
[0042] In a second aspect, the present application provides a method for preparing dry powder machine-made sand low-carbon concrete, which adopts the following technical solution:
[0043] A method for preparing dry powder machine-made sand low-carbon concrete comprises the following steps:
[0044] Cement, fly ash, mineral powder, recycled glass powder, nano calcium carbonate, silica fume, composite powder material, machine-made sand and crushed stone are mixed and stirred evenly to obtain a dry mix; then water and admixtures are mixed with the dry mix and stirred evenly to obtain low-carbon concrete.
[0045] By adopting the above technical scheme, the above preparation method has the advantages of being simple and easy to operate. The prepared concrete has good strength and durability, and can effectively utilize other industrial waste and agricultural solid waste, thereby reducing the use of cement, and thus greatly reducing the carbon emissions of concrete in the production process, which is conducive to achieving low-carbon and environmentally friendly production requirements.
[0046] In summary, this application has the following beneficial effects:
[0047] 1. The present application adopts composite powder materials and other powder materials to replace part of the cementitious materials, which can reduce the cement dosage of each cubic meter of concrete by about 70% on the original basis, thereby greatly reducing the carbon emission of concrete in the production process, which is conducive to achieving low-carbon and environmentally friendly production requirements. The composite powder material is obtained by compounding activated limestone powder and modified rice husk ash. Activated limestone powder is obtained by grinding, calcining, curing and pulverizing limestone powder. Since the activity of limestone powder itself is low, it is not conducive to exerting its gelling properties. After activation, calcium carbonate particles are treated in a liquid phase state, and calcium carbonate can be evenly coated by sulfate powder, and then fully dispersed on the surface of calcium carbonate particles through steric effect and double electric layer effect. The distance between particles is increased, and the secondary coagulation of particles is reduced during dehydration and drying, thereby improving the reaction ability of calcium carbonate, and finally forming highly active activated limestone powder. Modified rice husk ash is obtained by soaking, calcining and pulverizing rice husks. Rice husks are recycled agricultural waste. Its use can reduce the waste of agricultural resources and reduce carbon dioxide emissions. In addition, modified rice husk ash is beneficial to improving the bonding force between various cementitious materials and aggregates, thereby ensuring the strength and durability of low-carbon concrete.
[0048] 2. In the present application, it is preferred to use sulfate powder to activate limestone powder, and the ground limestone powder and sulfate powder are calcined at 900-1250°C. During the calcination process, the calcium carbonate in the limestone powder will decompose into calcium oxide and carbon dioxide. At the same time, the sulfate in the sulfate powder will react with calcium oxide to generate calcium sulfate. This reaction will form a calcium sulfate phase in the calcined material, which increases the reactivity of the limestone powder. The calcined material is soaked in water and cured at 30-50°C. During the curing process, the calcium oxide in the calcined material will react with water to generate calcium hydroxide. Calcium hydroxide can further react with sulfate to form a more stable calcium sulfate phase. This process can further increase the reactivity of the limestone powder.
[0049] 3. The preparation method of the present application has the advantages of being simple and easy to operate. The prepared concrete has good strength and durability, and can effectively utilize other industrial waste and agricultural solid waste, thereby reducing the use of cement, and further greatly reducing the carbon emissions of concrete during the production process, which is conducive to achieving low-carbon and environmentally friendly production requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a flow chart of a method for preparing dry powder machine-made sand low-carbon concrete provided in this application. DETAILED DESCRIPTION
[0051] The present application is further described in detail below in conjunction with embodiments.
[0052] The cement is ordinary Portland cement; the specific surface area of fly ash is 300-400m 2 / kg, the ignition loss is not more than 2%; the average particle size of rice husk ash is 3μm, and the ignition loss is 10-30%; the average particle size of recycled glass powder is 1-5μm white transparent powder; the specific surface area of silica ash is 18000-20000m 2 / kg, and the loss on ignition is 2-4%; the mineral powder used is S95 grade slag powder, and the specific surface area is 400-4502 / kg; the components of the special admixture for low-carbon concrete are a combination of a high water-reducing component, a collapse-preserving component, a retarding component, a viscosity regulating component, and an air-entraining component; the limestone machine-made sand used has a bulk density of 1500-1800kg / m3 and an apparent density of 2400-2800kg / m3, and is continuously graded; the water used is tap water.
[0053] Preparation example of activated limestone powder
[0054] Preparation Example 1
[0055] An activated limestone powder is prepared by the following method:
[0056] S1. Grinding: Grind the limestone powder in a ball mill at a speed of 30 r / min for 1 h to form fine powder.
[0057] S2. Calcination: calcine the ground limestone powder and sulfate powder at 900° C. for 1 hour to obtain a calcined material; wherein the sulfate powder is magnesium sulfate powder, and the mass ratio of the limestone powder to the magnesium sulfate powder is 1:0.01.
[0058] S3. Soaking: Soak the calcined material in water and cure at 30°C for 24 hours.
[0059] S4. Powdering: After the curing is completed, the soaked slurry is dried and then ball-milled at a speed of 30 r / min for 2 h to obtain activated limestone powder.
[0060] Preparation Example 2
[0061] An activated limestone powder is prepared by the following method:
[0062] S1. Grinding: Grind the limestone powder in a ball mill at a speed of 30 r / min for 1 h to form fine powder.
[0063] S2. Calcination: calcine the ground limestone powder and sulfate powder at 1000° C. for 1 hour to obtain a calcined material; wherein the sulfate powder is barium sulfate powder, and the mass ratio of limestone powder to barium sulfate powder is 1:0.1.
[0064] S3. Soaking: Soak the calcined material in water and cure at 40°C for 24 hours.
[0065] S4. Powdering: After the curing is completed, the soaked slurry is dried and then ball-milled at a speed of 30 r / min for 2 h to obtain activated limestone powder.
[0066] Preparation Example 3
[0067] An activated limestone powder is prepared by the following method:
[0068] S1. Grinding: Grind the limestone powder in a ball mill at a speed of 30 r / min for 1 h to form fine powder.
[0069] S2. Calcination: calcine the ground limestone powder and sulfate powder at 1250° C. for 1 hour to obtain a calcined material; wherein the sulfate powder is copper sulfate powder, and the mass ratio of limestone powder to copper sulfate powder is 1:0.2.
[0070] S3. Soaking: Soak the calcined material in water and cure at 50°C for 24 hours.
[0071] S4. Powdering: After the curing is completed, the soaked slurry is dried and then ball-milled at a speed of 30 r / min for 2 h to obtain activated limestone powder.
[0072] Preparation Example 4
[0073] An activated limestone powder is prepared by the following method:
[0074] S1. Grinding: Grind the limestone powder in a ball mill at a speed of 30 r / min for 1 h to form fine powder.
[0075] S2. Calcination: calcine the ground limestone powder at 1250° C. for 1 hour to obtain a calcined material.
[0076] S3. Soaking: Soak the calcined material in water and cure at 50°C for 24 hours.
[0077] S4. Powdering: After the curing is completed, the soaked slurry is dried and then ball-milled at a speed of 30 r / min for 2 h to obtain activated limestone powder.
[0078] Preparation example of modified rice husk ash
[0079] Preparation Example 5
[0080] The rice husk is soaked in a NaOH solution with a mass concentration of 3% for 0.5 h, the straw is repeatedly washed with water and then dried, and then calcined at 600° C., and then pulverized with a ball mill to obtain highly active modified rice husk ash.
[0081] Preparation Example 6
[0082] The rice husk is soaked in a NaOH solution with a mass concentration of 4% for 0.7h, the straw is repeatedly washed with water and then dried, and then calcined at 800°C, and then pulverized by a ball mill to obtain highly active modified rice husk ash.
[0083] Preparation Example 7
[0084] The rice husk is soaked in a NaOH solution with a mass concentration of 5% for 1 hour, the straw is repeatedly washed with water and then dried, and then calcined at 1000°C, and then pulverized with a ball mill to obtain highly active modified rice husk ash.
[0085] Preparation Example 8
[0086] The rice husk is soaked in water for 1 hour, then calcined at 1000°C, and then pulverized using a ball mill to obtain highly active modified rice husk ash.
[0087] Example
[0088] Example 1
[0089] A dry powder machine-made sand low-carbon concrete, the raw material components and corresponding amounts of which are shown in Table 1, wherein the composite powder materials are the activated limestone powder of Preparation Example 1 and the modified rice husk ash of Preparation Example 5.
[0090] The preparation steps are as follows:
[0091] Cement, fly ash, mineral powder, recycled glass powder, nano calcium carbonate, silica fume, composite powder material, machine-made sand and crushed stone are mixed and stirred for 2 minutes to obtain a dry mix. Then water and admixtures are mixed with the dry mix and stirred for 3 minutes to obtain low-carbon concrete.
[0092] Example 2
[0093] A dry powder machine-made sand low-carbon concrete, the raw material components and corresponding amounts of which are shown in Table 1, wherein the composite powder materials are the activated limestone powder of Preparation Example 2 and the modified rice husk ash of Preparation Example 6.
[0094] The preparation steps are as follows:
[0095] Cement, fly ash, mineral powder, recycled glass powder, nano calcium carbonate, silica fume, composite powder material, machine-made sand and crushed stone are mixed and stirred for 2 minutes to obtain a dry mix. Then water and admixtures are mixed with the dry mix and stirred for 3 minutes to obtain low-carbon concrete.
[0096] Example 3
[0097] A dry powder machine-made sand low-carbon concrete, the raw material components and corresponding amounts of which are shown in Table 1, wherein the composite powder materials are the activated limestone powder of Preparation Example 3 and the modified rice husk ash of Preparation Example 7.
[0098] The preparation steps are as follows:
[0099] Cement, fly ash, mineral powder, recycled glass powder, nano calcium carbonate, silica fume, composite powder material, machine-made sand and crushed stone are mixed and stirred for 2 minutes to obtain a dry mix. Then water and admixtures are mixed with the dry mix and stirred for 3 minutes to obtain low-carbon concrete.
[0100] Table 1 Raw material components and weights (kg) in Examples 1-3
[0101]
[0102]
[0103] Example 4
[0104] A dry powder machine-made sand low-carbon concrete, which is different from Example 3 in that the activated limestone powder in the composite powder material is the activated limestone powder prepared in Preparation Example 4.
[0105] Example 5
[0106] A dry powder machine-made sand low-carbon concrete, which is different from Example 3 in that the modified rice husk ash in the composite powder material is the modified rice husk ash prepared in Preparation Example 8.
[0107] Comparative Example
[0108] Comparative Example 1
[0109] A dry powder machine-made sand low-carbon concrete, which is different from Example 3 in that: no nano calcium carbonate is added to the raw materials of this comparative example.
[0110] Comparative Example 2
[0111] A dry powder machine-made sand low-carbon concrete is different from Example 3 in that an equal amount of activated limestone powder is used in the raw materials of this comparative example instead of modified rice husk ash, that is, 90 kg of activated limestone powder is selected as the composite powder material.
[0112] Comparative Example 3
[0113] A dry powder machine-made sand low-carbon concrete is different from Example 3 in that an equal amount of modified rice husk ash is used in the raw materials of this comparative example instead of activated limestone powder, that is, 90 kg of modified rice husk ash is used as the composite powder material.
[0114] Performance testing
[0115] Detection Methods
[0116] The low-carbon concrete prepared in Examples 1-5 and Comparative Examples 1-3 was made into 150mm×150mm×150mm cubic standard test blocks as test blocks, and 3 standard test blocks were cast in each group. The standard test blocks were then placed in a standard curing room for curing. After 28 days, the three standard test blocks were tested using a pressure testing machine according to the compressive strength test in GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete"; the arithmetic mean of the values obtained from the three tests was taken as the test value of the group of recycled concrete test blocks. The test results are shown in Table 2.
[0117] Table 2 Compressive strength test results
[0118] project Example 1 Example 2 Example 3 Example 4 Compressive strength / MPa 43.3 43.5 43.8 36.5 project Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Compressive strength / MPa 35.3 25.6 31.2 28.6
[0119] Combining Examples 1-3 and Table 2, it can be seen that the compressive strength of the low-carbon concrete prepared by the composite powder material in the present application is maintained at a relatively stable state, basically maintained at about 43.5MPa. To achieve the same level of compressive strength, the cement dosage of the concrete in the prior art must basically reach 200kg / m 3The above, and this application uses composite powder materials and other cementitious materials in combination, the final cement dosage is about 25kg per cubic meter, under the same strength level, the cement dosage is reduced by about 70%, thereby greatly reducing the carbon emissions of concrete during the production process. And it can also recycle agricultural solid waste such as rice husk ash, which is conducive to achieving low-carbon and environmentally friendly production requirements.
[0120] Combining Examples 3-5 and Table 2, it can be seen that since the raw materials in the composite powder materials of Examples 4 and 5 were prepared by different methods, the compressive strength of the concrete was reduced to varying degrees. Since the activated limestone powder in Example 4 was not activated by adding sulfate powder during the preparation process, the activation activity of the limestone powder was poor, which led to a decrease in the strength of the prepared concrete. Since the modified rice husk powder in Example 5 was not soaked in NaOH solution during the preparation process, a large amount of impurities adhered to the rice husk ash, which made it impossible to exert its good cementing properties, thereby reducing the strength of the concrete.
[0121] Combining Example 3, Comparative Example 1 and Table 2, it can be seen that since nano calcium carbonate is not added during the preparation of the low carbon concrete in Comparative Example 1, it is not conducive to improving the bonding force between various cementitious materials and aggregates, which leads to a decrease in the strength performance of the low carbon concrete.
[0122] It can be seen from Example 3, Comparative Example 1, Comparative Example 2 and Table 2 that the use of activated limestone powder and modified rice husk ash alone cannot exert their optimal cementing properties, resulting in a large loss in the compressive strength of the concrete. Therefore, the composite use of activated limestone powder and modified rice husk ash can better replace the cementitious bonding effect of cement, thereby reducing the amount of cement while ensuring that the concrete has better strength and durability, thereby achieving the low-carbon and environmentally friendly industry requirements.
[0123] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A dry powder machine-made sand low-carbon concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of cement; 30-60 parts of fly ash; 30-60 parts of mineral powder; Recycle glass powder 10-30 parts; 30-60 parts of nano calcium carbonate; Silica fume 10-30 parts; 70-90 parts of composite powder material; 600-800 parts of machine-made sand; 800-1000 parts of crushed stone; 150-157 parts of water; 5-10 parts of admixture; The composite powder material is obtained by mixing activated limestone powder and modified rice husk ash; The activated limestone powder is obtained by grinding, calcining, curing and pulverizing limestone powder; The modified rice husk ash is obtained by soaking, calcining and pulverizing rice husk; The activated limestone powder is prepared by the following method: S1. Grinding: Grind the limestone powder in a ball mill to form fine powder; S2, calcination: calcining the ground limestone powder and sulfate powder at 900-1250° C. for 1-2 hours to obtain a calcined material; S3, soaking: soak the calcined material in water and cure it at 30-50°C; S4, pulverization: after the curing is completed, the soaked slurry is dried and then ball-milled to obtain activated limestone powder; The sulfate powder in S2 is any one of magnesium sulfate, barium sulfate and copper sulfate; The mass ratio of limestone powder to sulfate powder in S2 is 1:(0.01-0.2).
2. The dry powder machine-made sand low-carbon concrete according to claim 1, characterized in that: The weight percentage of activated limestone powder in the composite powder material is 50-70%.
3. The dry powder machine-made sand low-carbon concrete according to claim 1, characterized in that: The modified rice husk ash is prepared by the following method: The rice husk is soaked in a NaOH solution for 0.5-1h, repeatedly rinsed with water and then dried, then calcined at 600-1000°C, and then pulverized to obtain highly active modified rice husk ash.
4. The dry powder machine-made sand low-carbon concrete according to claim 3, characterized in that: The mass concentration of the NaOH solution is 3-5%.
5. A method for preparing a dry powder machine-made sand low-carbon concrete according to any one of claims 1 to 4, characterized in that: The steps include: Cement, fly ash, mineral powder, recycled glass powder, nano calcium carbonate, silica fume, composite powder material, machine-made sand and crushed stone are mixed and stirred evenly to obtain a dry mix; then water and admixtures are mixed with the dry mix and stirred evenly to obtain low-carbon concrete.
Citation Information
Patent Citations
High-performance concrete gel material for tunnel and application thereof
CN102838323A
Low-carbon cementing material and method for preparing concrete
CN107572841A
Admixture, concrete prepared therefrom and preparation methods for admixture and concrete prepared therefrom
CN108911544A